(untitled) (Fiep Bulletin - online, 2011)
The dance is artistic expression inherent in man, present in their culture as a form of expression since the dawn of humanity. Dancing in the educational setting is educational, it is a universal art of cultural value, which encourages the biopsychosocial development. We sought to investigate the use of dance in the context of physical education in schools and its presence as a content area. Characterized as exploratory and descriptive study was conducted the literature review and application of interviews with teachers and students. The sample comprised 33 people, including 26 students in a school hall and seven physical education teachers from public and private schools, all of the city of Fortaleza. The study confirmed that in school, dance is present as an extracurricular activity and predominantly on festive occasions, these experiences are respectively the experience of 26% and 15% of students studied. The lack of experience and mastery of content, along with the low receptivity of the students were the justifications given by 71% of teachers that do not include dance in their classes. The results lead us to question what kind of training is happening in the banks academics. It is necessary to carry out studies on the related training courses related to dance, to discover and correct this shortcoming teaching Physical Education.